Dynamic and Challenges of Women Leaders: Gender Equality Agenda vs Gender Traditional Roles In Society - Serlyeti Pulu; Nur Iman Subono; Shelly Adelina (Sunan Kalijaga State Islamic University & The Asia Foundation, 2023)
Artikel ini mengkaji beberapa penelitian terdahulu tentang latarbelakang dan konteks social membentuk perempuan pemimpin dalam gerakan sosial-politik dan gerakan perempuan, agenda-agenda aksi yang dirumuskannya, serta bagaimana mereka mengelola tantangan yang dihadapi dalam menjalankan misinya. Fenomena munculnya perempuan pemimpin di berbagai organisasi sosial dan organisasi perempuan di tingkat lokal dan di tingkat nasional periode kontemporer dan periode pergerakan kemerdekaan menjadi konteks kajian dalam penulisan ini. Kerangka pemberdayaan dari Joana Rowlands memandu analisis tulisan ini. Temuan penting kajian atas riset-riset terdahulu menunjukkan bahwa perempuan pemimpin mengembangkan kekuatan dari dalam diri sendiri, memperkuatnya dengan membangun hubungan dengan pihak lain, dan selanjutnya mengembangkan aksi bersama. Kekuatan yang sudah dimiliki tersebut, berinteraksi dengan persoalan sosial, menghasilkan aksi kolektif, merupakan proses hasil pemberdayaan yang menjadikan para perempuan dapat mendorong perubahan yang lebih besar. [This article examines some of the previous research on the background and social context of shaping women leaders in socio-political movements and women’s movements, the action agendas they formulated, and how they manage the challenges faced in carrying out their missions. The phenomenon of the emergence of women leaders in various social organizations and women’s organizations at the local level and the national level of the contemporary period and the period of the independence movement is the context of the study in this paper. The empowerment framework from Joana Rowlands guides the analysis. Key findings from previous studies have shown that women leaders develop strengths from within themselves, strengthen them by building relationships with others, and further develop collective action. These strengths, interacting with social issues, and generating collective action, are processes of empowerment that allow women to drive greater change.]